Uji Efektivitas Alih Fungsi Perangkap Ikan Model Bubu Menjadi Perangkap Hama Keong Mas (Pomacea canaliculata L.) dengan Berbagai Atraktan Biologi - Putri Rahayu; Nurul Istiqomah; Farida Adriani (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2018)
Golden snail or murbei snail is one of the important pests of rice plants because the damage caused can reach an intensity of 13,2-96,5%. The results of the south Kalimantan BPTPH observation of golden snail attacks in the north Hulu Sungai Utara Regency increased from 0,3 ha in 2015 to 1 ha in 2016. One of the controls of golden snail pest which uses fish traps in bubu, bait is one of the important factors to support the success of a fishing operation with traps and fishing rods. Attractant plants are chemical compounds that act as bait against pests, the use of attractant plants to attract snails is one the most environmentally friendly ways to control it. This research was conducted in the village of Pakacangan districts Amuntai Hulu Sungai Utara. Research using Randomized Block Design (RBD), grouping based on the water level. The factors studied were planted type (A), which consisted of 4 levels, namely: a1= papaya leaves, a2= taro leaves, a3= dried onions leaves, and a4= cassava leaves. The results showed that various attractant plants had no effect on the amount of golden snail 5, 10, and 15 days after installation, but had a significant effect on the weight of the feed residue, the total weight of the feed and the length of the feed.